2012
DOI: 10.1177/0278364911432895
|View full text |Cite
|
Sign up to set email alerts
|

Active Handrest: A large workspace tool for precision manipulation

Abstract: To address the limited dexterous workspace of the human hand, we have developed the Active Handrest. This device assists in precision manipulation tasks by extending a user’s dexterous workspace while providing ergonomic support for reduced fatigue. People use handrests to complete dexterous activities as routine as providing a signature. However, the dexterous workspace of the statically supported hand is somewhat limited. By providing consistent support over large workspaces the Active Handrest could be usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 30 publications
6
16
0
Order By: Relevance
“…In our previous works [7,8,9] we demonstrated that the Active Handrest is able to provide increased task accuracy over freehand, fixed supports, and passive supports. In this paper we discuss two experiments investigating factors that aid in accurate labyrinth navigation and to determine the effectiveness of adaptive admittance and virtual fixtures for the Active Handrest.…”
Section: Methodsmentioning
confidence: 83%
See 4 more Smart Citations
“…In our previous works [7,8,9] we demonstrated that the Active Handrest is able to provide increased task accuracy over freehand, fixed supports, and passive supports. In this paper we discuss two experiments investigating factors that aid in accurate labyrinth navigation and to determine the effectiveness of adaptive admittance and virtual fixtures for the Active Handrest.…”
Section: Methodsmentioning
confidence: 83%
“…The focus of the experiments discussed herein is to explore the effectiveness of various adaptive admittance control and virtual fixture methods, and to quantify the performance differences between the Active Handrest and freehand, over a variety of conditions. In these experiments, static and passive handrests were not examined as our previous works [7,9] already showed the relative benefit of the Active Handrest compared to these support methods. The motivation of our experiments is to show the potential for the use of these methods on the Active Handrest to improve accuracy while maintaining or improving task completion times.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations